A brief introduction to fluid mechanics - Young, Donald F. (John Wiley & Sons, 1997)
An introduction to fluid mechanics. Example problems with detailed solutions are provided throughout the text, they include everyday situations which allow the reader to gain confidence in solving problems and reinforce the concept that fluid mechanics is an important part of our world.